Theory and practice of Arena face detection and recognition system - Zhao, Zixiao (2016)
Face is one of the most unique biometrics for identification verification. Nowadays many projects are undertaken to realize an effective way for quickly identifying human faces through studies of manifold techniques and machine learning. Unlike these newly innovated complex algorithms target at mass-scale system of enterprise level, most of which have not been published to open source platform, This project aims to use a rather state-of-art system, ARENA, to handle a classical real time webcam face verification task in reality, as a feasible and open source solution for face verification in daily individual use under an acceptable budget, while helping readers build fundamental notions of classical face recognition utilization. The implementation of this system will be based on C++ language as primary programming language( to maintain data structure ), Qt user interface to build GUI, and OpenCV for all image processing tasks under a basis of the MVC principle (Model, View, Controller) as shown in the figure 1 below.